Increased neural processing of rewarding and aversive food stimuli in recovered anorexia nervosa. - Cowdrey, F; Park, R; Harmer, C; Mccabe, C (2011)
BACKGROUND: Recent evidence has shown that individuals with acute anorexia nervosa and those recovered have aberrant physiological responses to rewarding stimuli. We hypothesized that women recovered from anorexia nervosa would show aberrant neural responses to both rewarding and aversive disorder-relevant stimuli. METHODS: Using functional magnetic resonance imaging (fMRI), the neural response to the sight and flavor of chocolate, and their combination, in 15 women recovered from restricting-type anorexia nervosa and 16 healthy control subjects matched for age and body mass index was investigated. The neural response to a control aversive condition, consisting of the sight of moldy strawberries and a corresponding unpleasant taste, was also measured. Participants simultaneously recorded subjective ratings of "pleasantness," "intensity," and "wanting." RESULTS: Despite no differences between the groups in subjective ratings, individuals recovered from anorexia nervosa showed increased neural response to the pleasant chocolate taste in the ventral striatum and pleasant chocolate sight in the occipital cortex. The recovered participants also showed increased neural response to the aversive strawberry taste in the insula and putamen and to the aversive strawberry sight in the anterior cingulate cortex and caudate. CONCLUSIONS: Individuals recovered from anorexia nervosa have increased neural responses to both rewarding and aversive food stimuli. These findings suggest that even after recovery, women with anorexia nervosa have increased salience attribution to food stimuli. These results aid our neurobiological understanding and support the view that the neural response to reward may constitute a neural biomarker for anorexia nervosa.